Environmental law : the law and policy relating to the protection of the environment - "Ball, Simon" (London, 1991)
This book with its clear and up to date description of the Environmental law. The authors emphasise how the law works in practice, placing it in its practical context and describing the various remedies which are available. They emphasise the fundamental importance of environmental policy and the exercise of discretion.
Keywords: Environment law